Habits Reflected in American Action Films - Abood, Shahad Haider; Al Kaabi, Raad Jasim (ALBAHITH ALALAMI, 2023)
The research aims to identify the predominant habits and behaviors promoted by American action films frequently streamed on Cinemana website—a specialized platform for streaming films and series as the most followed platform. This platform offers a range of film genres, including the latest releases, free of charge. Using a simple random sampling method, twenty action films were selected for the study. Consequently, the researcher opted for a descriptive-analytical approach, deemed most appropriate for achieving the research objectives, employing content analysis as a tool to scrutinize these films. The findings highlighted that behavioral habits associated with scenes of violence, destruction, sabotage, revenge, and threats ranked highest. The results pertaining to behavioral habits like murder scenes and threats also emerged prominently in the analytical study, indicating their negative influence by ingraining such habits and integrating them into an individual's daily behavior.